Impacts of Al2O3 Doping on Microstructure, Phase Constitution and Microwave Dielectric Properties of Ca0.61Nd0.26TiO3 Ceramics. Issue 2 (3rd April 2017) - Zhong, Chaowei; Tang, Bin; Tan, Yidong; Zhang, Shuren
Abstract : The effects of Al2 O3 addition on microstructure, phase evolution and microwave dielectric properties of Ca0.61 Nd0.26 TiO3 – x mol Al2 O3 ( x = 0, 0.025, 0.05, 0.075, 0.1) ceramics have been investigated in this study. With x increasing from 0 to 0.05, the system maintained a single perovskite phase while bulk density decreased rapidly due to grain size degradation. Correspondingly, dielectric constant (ϵr ) decreased from 103 to 79.2 and temperature coefficient of resonant frequency (τ f ) dropped from +247 to +159.3 ppm/°C. Moreover, anti-reduction of Ti 4+ gave rise to a nearly doubled Q × f value, from 8600 to 15500 GHz. For 0.075≤x≤0.1, X-ray diffraction results showed a secondary phase whose peaks were consistent with Ca2 Nb2 O7 phase, resulting in decreased microwave dielectric properties. GRAPHICAL ABSTRACT: